miR-409-3p inhibits the proliferation and migration of human ovarian cancer cells by targeting Rab10 - Li, Yanyi; Chen, Li; Zhang, Beibei; Ohno, Yuko; Hu, Hua (Cellular and Molecular Biology, 2020)
Ovarian cancer is a leading cause of gynecological cancer-related mortality. It has been reported that miR-409-3p is involved in the proliferation and migration of cancer cells. However, the role of miR-409-3p in ovarian cancer has not been well studied. The present study aimed to investigate the functional role of miR-409-3p in the pathogenesis of ovarian cancer, and its potential mechanism. It was found that the expression levels of miR-409-3p in 6 ovarian cancer tissues were upregulated. Through proliferation, migration and colony formation assays, it was revealed that overexpression of miR-409-3p inhibited the proliferation and migration of ovarian cancer cells. It was predicted from bioinformatics assays that the complementary binding sites were within miR-409-3p and Rab10. It was also demonstrated that the downregulation of the expression of Rab10 reversed the miR-409-3p downregulation-induced abnormal proliferation of ovarian cancer cells. These results suggest that miR-409-3p expression can be used as a predictive marker for the prognosis of ovarian cancer. Thus, the miR-409-3p/Rab10 axis may be a novel therapeutic target for ovarian cancer.